Preliminary results on the daily and seasonal rhythms of cuttlefish Sepia officinalis (Linnaeus, 1758) locomotor activity in captivity - Oliveira, Catarina (2017)
Cephalopods are considered as an alternate group for aquaculture species diversification [1,2], not only because they are a good food source (highly appreciated in some worldwide markets, e.g., Portugal, Spain, Italy and Asia) and have the potential to quickly reach a market size, but also because they are considered animal models in several fields of research [3–5], and it is expected that such models are progressively obtained from bioteriums instead of being captured from nature. Despite the recent advances in culture protocols of several cephalopod species [2], there is still little information available about the biological rhythms of cephalopods in captivity. In fact, to the best of our knowledge, there are only 4 published papers concerning this theme, and these are focused on octopus species [6–9]. This issue assumes increasing importance with the enforcement of EU welfare legislation (Directive 2010/63/EU), and this information is critical for the future update of Annex III (housing conditions) for cephalopods of that Directive, and for a future update of the Guidelines for the Care and Welfare of Cephalopods in Research [10]. If it is considered that the European cuttlefish Sepia officinalis (Linnaeus, 1758) may have, at the least, two different sleep‐like states [11], the importance of this study becomes even more evident.